Flame Synthesis of Nanocrystalline Zirconia and Yttria Stabilised Zirconia (YSZ) Composites Using Inorganic Precursors. (2018) - Verma, Sourabh; Manjith Kumar, B.; Bhattacharya, S.S.
Abstract: The flame synthesis route has been considered as a versatile and promising technique for the preparation of various types of submicrocrystalline and nanocrystalline ceramic materials in large quantities. However, a majority of these techniques use volatile metalorganic precursors, which have handling issues. On the other hand, inexpensive metal salts, like nitrates, which are safer, cheaper and easily available could also be used. In this investigation, the synthesis of pure nanocrystalline zirconia and single-step synthesis of yttria stabilised zirconia nanocomposites with systematically varying yttria content were attempted using inorganic precursors in an indigenously fabricated flame reactor system. The synthesized powders were characterized for their crystallite sizes, phase content, composition, particle shape and morphology using standard equipment. The dependence of the particle morphology and size-distribution upon the precursor concentration and solvent was studied.